Relativistic Toda Chain with Boundary Interaction at Root of Unity - Iorgov, N.; Roubtsov, V.; Shadura, V.; Tykhyy, Y. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We apply the Separation of Variables method to obtain eigenvectors of commuting Hamiltonians in the quantum relativistic Toda chain at a root of unity with boundary interaction.